Educational Innovation Through the Independent Learning Initiative in Indonesia - fitriyah, Aidatul; Aminah, Ummi; Safitri, Awalina Dea (Indonesian Scientific Publication, 2024)
This study systematically reviews how Indonesia's Merdeka Belajar Initiative and innovative pedagogy close the gap between access to education and learning quality. It explores how these reforms equip students with critical thinking and problem-solving skills for the digital era. The author analyzed recent academic studies, policy documents, and international reports to evaluate the initiative's goals, innovative teaching practices, and their impact on educational outcomes in Indonesia. This research finds that the Merdeka Belajar Initiative shifts Indonesia’s education system towards autonomy, flexibility, and student-centered learning. Differentiated instruction, project-based learning, and gamification significantly enhance critical thinking and student engagement. However, teachers face challenges such as inadequate preparation, resource disparities, and resistance to change. Our findings highlight the importance of providing continuous professional development, strengthening technological infrastructure, and creating a national framework that accommodates regional diversity. It can be concluded that the Merdeka Belajar initiative and innovative pedagogy have the potential to transform Indonesia’s education system. These reforms enhance academic performance and holistic student development. Overcoming systemic barriers and strengthening policy support will ensure their success. This study emphasizes the need to align educational reform with innovative teaching practices to prepare students for the demands of the 21st century. It provides actionable insights for policymakers, educators, and researchers to improve education quality and equity in Indonesia.